Estudo do efeito de tratamento enzimático sobre as características de qualidade de ardósia e sua influência no aroma de chocolate - Nascimento, Hilana Salete Silva Oliveira (2015)
A recurring problem in the chocolate industry is the low quality of cocoa beans, which influences the chocolate aroma. One possibility to contribute to solve this problem is the application of commercial exogenous enzymes on slate. This work proposed detection and sequencing, by mass spectrometry, of the peptides present in slates subjected to treatment with microbial enzyme proposed by Oliveira et al. (2011). Associated to the analysis of peptides was studied the concentration of phenolic compounds and antioxidant activity since the reduction of phenolics in cocoa processing steps is known to cause reduction of astringency and bitterness contributing to the formation of important compounds for the chocolate aroma. The results indicate that although the qualitative standard of the hydrophobic amino acids present in the peptides responsible for the mixture of chocolate aroma is more important than the quantitative standard, the presence of the amino acids leucine, alanine, phenylalanine, and tyrosine in appropriate amounts is essential for obtaining desired aroma. The proposed treatment caused a reduction in the phenolics concentration, which is desirable for a chocolate aroma, and in antioxidant activity. In general, the profile peptide, the phenolic content and antioxidant activity of treated slate resembled more good quality almonds suggesting the effectiveness of the proposed treatment. Research the market and trends indicated favorable conditions for diffusion of the proposed treatment in the process industries.